EICOSANOIDS in HUMAN PHYSIOLOGY: POLYUNSATURATED FATTY ACID SOURCES, BIOSYNTHESIS, FUNCTIONS, and THERAPEUTIC IMPLICATIONS - Ekin, İhsan (Abdülkadir IŞIK, 2023)
This comprehensive review explores the sources, biosynthesis, transport, and multifaceted functions of eicosanoids in human physiology. Eicosanoids, encompassing prostaglandins, thromboxanes, leukotrienes, lipoxins, and their oxygenated derivatives, are lipid mediators derived from C20 polyunsaturated fatty acids, primarily belonging to the omega-6 and omega-3 families. Arachidonic acid, a major precursor, serves as the primary building block for prostaglandins and other eicosanoids. It is stored in cell membrane phospholipids, predominantly in phosphatidylinositol and other complex lipid forms. The release of free arachidonic acid is facilitated by the enzyme phospholipase A2. Eicosanoids exert diverse biological functions within vertebrates, participating in crucial endocrine processes such as inflammation, reproduction, gastric secretion, and blood pressure regulation. Moreover, they contribute to homeostasis maintenance by modulating vascular permeability, safeguarding gastric mucosal integrity, and regulating platelet aggregation. Notably, eicosanoids exhibit both pro-inflammatory and anti-inflammatory properties, engaging in complex regulatory networks involving immune cells and the microenvironment. They also play significant roles in neural cell crosstalk, atherosclerosis, cancer development, platelet activation, and allergic/asthmatic diseases. Understanding the intricate mechanisms and interactions of eicosanoids holds great potential for targeted therapeutic interventions. Further research in this field can provide valuable insights into their precise roles and aid in the development of novel treatments for a wide range of diseases.
Keywords: Health Services and Systems (Other); Sağlık Hizmetleri ve Sistemleri (Diğer)